BMI as a moderator of the relationship between global self-esteem or self-perceived physical attractiveness and jealousy among women - Paulina Banaszkiewicz; Karolina Górnik-Horn (Journal of Modern Science)
Objectives The aim of the study was to determine whether global self-esteem and physical attractiveness related self-esteem are predictors of jealousy intensity, and whether body mass index moderates the relationship between these aspects of self-esteem and jealousy.